Studi Timbulan, Komposisi Dan Karakteristik Fisika Dan Kimia (Proximate Analysis) Sampah Non Domestik Di Kecamatan Tampan Kota Pekanbaru - Sari, Siti; Yenie, Elvi; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Increased community activities will increase the amount of waste generated. Tampan District is one of a small town in the city of Pekanbaru can not be separated from tge garbage thing. This research aims to determine the generation, composition and physical characteristics and chemical (proximate analysis) non domestic garbage in Tampan of District Pekanbaru of City and generation data, composition and physical characteristics and chemical (proximate analysis) garbage are indispensable in designing of garbage management system. This research was conducted in 37 places including 19 institutions ( 8 schools, 5 offices and 6 health centers), 11 commercials garbage (6 stores, 1 markets, 2 restaurants and 2 hotels), 1 street sweeping and 6 industrials. Determination of non-domestic garbage generation is performed by interviewing and sampling of garbage at source based methode SNI 19-3964-1994 performed for eight day in a row. The results study of non-domestic generation of Tampan District Pekanbaru City in the amount of 0,38 kg/p/d in of weight unit or 4,13 l/p/d in volume unit. The composition of non domestic Tampan of District Pekanbaru of City solid waste domination of organic waste about 60,94% and anorganic garbage composition of 39,06%. For Physical characteristics such as specific weight is 0,23 kg/l and composition factor is 1,38 litre. The chemical characteristics (proximate analysis) are moisture 26,2%, volatile rate 54,6%, ash rate 9,5% and 10,0% fixed carbon rate.Key words : non domestic solid waste, waste generation composition, physical characteristic, chemical characteristic (proximate analysis).